First record of the moorland clouded yellow Colias palaeno (Linnaeus, 1761) (Lepidoptera: Pieridae) in Altai Krai (Russia, West Siberia) with notes on its DNA barcode - Kuftina, Galina N.; Shapoval, Nazar A.; Yakovlev, Roman V.; Krupitsky, Anatoly V.; Kuvaev, Andrey V.; Masharsky, Alexey E. (Acta Biologica Sibirica, 2020)
Colias palaeno (Linnaeus, 1761) is reported from Altai Krai for the first time. The DNA barcode of the collected specimen was analysed and compared with molecular data on European populations of C. palaeno available in the public databases GenBank (http://www.ncbi.nlm.nih.gov) and BOLD (http://www.boldsystems.org). The molecular analysis has shown that the specimen from Altai Krai shares mitochondrial barcode with some specimens from mountain populations of the Alps and the Czech Republic, and differs significantly from lowland populations of C. palaeno from Central and Northern Europe.